Compliance oversight and its role in verifying the efficiency of use of emergency funding in light of crises (Journal of Accounting and Financial Studies ( JAFS ), 2024)
In light of the Covid-19 pandemic, governments around the world have taken emergency measures to protect their citizens and ensure the continuity of the work of their institutions. Among these measures is the allocation of emergency funding to purchase medical, therapeutic and preventive supplies. The role of the Supreme Audit and Accounting Institutions has emerged in conducting oversight operations to investigate the extent to which... Compliance with good protection measures and their effectiveness at the beginning of oversight work in light of crisis management by relying on the application of the standards of the International Organization of Supreme Audit Institutions (INTOSAI), especially in the field of compliance oversight in light of disasters and crises through the application of control procedures in accordance with the oversight standard (4000) for verification. Regarding the proper use of public funds in light of the emergency (Corona pandemic), the research concluded that compliance oversight plays an important role in ensuring the proper use of emergency funding to confront the Covid-19 pandemic. The results also showed that the commitment of SAIs to international standards for SAIs, in particular Standard (4000) to verify the integrity of the agreement, that in exercising compliance control under emergency circumstances, the auditor must exercise more professional care, since the business environment in light of the Corona epidemic and emergency events increases the risk of fraud or a decrease in compliance with the legal, legislative and regulatory frameworks and the actions that accompany confronting the epidemic, which It enhances the quality of oversight tasks and contributes to achieving the principles of transparency, accountability, and inclusion